A GLIMPSE OF PHYSICS - Liek Wilardjo (Fakultas Teknik Elektronika dan Komputer Universitas Kristen Satya Wacana, 2013)
Three stories are told, interspersed by two interludes. The first story is about Einstein’s mass-energy equivalent, the second is on De Broglie’s particle-wave duality, and the third is the perennial controversy of determinism versus probabilism. The first interlude gives Pythagorean theorem and Socratic anamnetic questions, whilst the second is a brief account of Philosophy of Science focused on paradigm and values. Through the stories and their interludes attempt is made to give just a glimpse of Physics.